2004
DOI: 10.2136/sssaj2004.1750
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Distribution in a Hummocky Landscape from Saskatchewan, Canada

Abstract: Changes in the topography influence organic and inorganic C contents and δ13C values of soil C across a landscape. The objectives of this research were to: (i) study the effect of landscape on the formation and distribution of pedogenic carbonate and organic matter distribution in a hummocky landscape, and (ii) estimate the amount of organic C and pedogenic carbonate accumulation in local scale in comparison with regional scale using the stable isotope geochemistry techniques and standard characterization anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
5
29
0
1
Order By: Relevance
“…Furthermore, as described above, patterned ground features can exhibit various combinations of these suborder soils, resulting in large local and landscape heterogeneity. A number of studies have looked at the SOC content of patterned ground features, for example frost boils (Dyke and Zoltai, 1980;Walker et al, 2004;Kaiser et al, 2005;Michaelson et al, 2012), circles (Kimble et al, 1993;Hallet and Prestrud, 1986), stripes (Walmsley and Lavkulich, 1975;Horwath et al, 2008), icewedge polygons Zubrzycki et al, 2013), and earth hummocks (Kimble et al, 1993;Landi et al, 2004). In addition to these pedon-scale studies, explicit efforts to account for and incorporate local-scale spatial heterogeneity into sampling designs and upscaling approaches are being explored for the estimation of SOC stocks on landscape or regional scales (Horwath et al, 2008;Hugelius and Kuhry, 2009;Zubrzycki et al, 2013).…”
Section: Quantity Of Organic Carbon In Permafrost Soilsmentioning
confidence: 99%
“…Furthermore, as described above, patterned ground features can exhibit various combinations of these suborder soils, resulting in large local and landscape heterogeneity. A number of studies have looked at the SOC content of patterned ground features, for example frost boils (Dyke and Zoltai, 1980;Walker et al, 2004;Kaiser et al, 2005;Michaelson et al, 2012), circles (Kimble et al, 1993;Hallet and Prestrud, 1986), stripes (Walmsley and Lavkulich, 1975;Horwath et al, 2008), icewedge polygons Zubrzycki et al, 2013), and earth hummocks (Kimble et al, 1993;Landi et al, 2004). In addition to these pedon-scale studies, explicit efforts to account for and incorporate local-scale spatial heterogeneity into sampling designs and upscaling approaches are being explored for the estimation of SOC stocks on landscape or regional scales (Horwath et al, 2008;Hugelius and Kuhry, 2009;Zubrzycki et al, 2013).…”
Section: Quantity Of Organic Carbon In Permafrost Soilsmentioning
confidence: 99%
“…Soil moisture is also strongly influenced across the landscape by topography, which may change spatial patterns of water runoff and deposition (Horton 1933;Meeuwig 1970;Bork et al 2001;Salve and Allen-Diaz 2001), as well as evaporation through surface exposure to solar radiation (Chapin et al 2002). Finally, landscape position influences soil texture and organic matter, further modifying water-holding capacity and infiltration, and changing hydrologic properties of the local ecosite (Landi et al 2004). Nonetheless, few if any of these factors can be readily manipulated to increase soil moisture through land management practices.…”
Section: Introductionmentioning
confidence: 99%
“…The principle that underpins landform segmentation is that many hydrological, and hence soil processes, are related to topographic attributes such as elevation, slope, aspect, and plan and profile curvature (Wysocki et al, 2000;Gallant and Wilson, 1996). Many studies have shown (Landi et al, 2004;Singh and Kar, 2001;King et al, 1999) that even subtle differences in topography can have a large effect on the spatial distribution of soil properties. Although these soil-geomorphic associations have conceptually been recognized for decades (Young and Hammer, 2000), landform segmentation enables rapid quantification and spatial analysis of the relationships, which can then be utilized for partitioning variability and ultimately predicting soil or other ecosystem properties.…”
Section: Introductionmentioning
confidence: 99%